Pengaruh Asupan Makanan dan Stress terhadap Kondisi Kesehatan Pasien Kemoterapi: Effect of Food Intake and Stress on Health Conditions of Chemotherapy Patients - Susilawati Susilawati; Rifa Nurafifah Syabaniah; Rina Riniawati (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Cancer is a disease that requires treatment with a long process. Types of treatment include chemotherapy. Cancer patients who are undergoing chemotherapy treatment are usually advised to maintain their health condition. Fulfillment of nutritious and balanced nutrition and avoiding stress are the best steps to support the chemotherapy process. The purpose of this study was to determine how much influence food intake and stress have on the health conditions of chemotherapy. The test results can be concluded that there is an influence between food intake and stress on the health condition of chemotherapy patients as evidenced by the results of the validity and reliability tests above 0.60 with a description of the value of variable X1, namely: food intake has a Cronbach value of 0.737 negligence with stress which is variable X2 with Cronbach alpha 0.633 to variable Y, namely health conditions. with a value of 0.820. Keywords: cancer, chemotherapy, validity and reliability tests.